2011
DOI: 10.3171/2011.10.focus11228
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of asymptomatic moyamoya arteriopathy in pediatric syndromic populations: radiographic and clinical progression

Abstract: Object Limited data exist to guide management of incidentally discovered pediatric moyamoya. Best exemplified in the setting of unilateral moyamoya, in which the unaffected side is monitored, this phenomenon also occurs in populations undergoing routine surveillance of the cerebral vasculature for other conditions, such as sickle cell disease (SCD) or neurofibromatosis Type 1 (NF1). The authors present their experience with specific syndromic moyamoya populations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 23 publications
3
47
1
Order By: Relevance
“…There is abundant evidence supporting the role for surgical revascularization of both symptomatic and asymptomatic moyamoya in children with operations such as pial synangiosis. [5][6][7][8] Regarding the MTS, the American Academy of Neurology practice parameter recommends surgery as the treatment of choice for medically intractable temporal lobe epilepsy. 4 The patient's seizures in this case were controlled with medication at the time of diagnosis of moyamoya, but the natural history of MTS suggests that a minority of children will continue to attain seizure control on medication alone, whereas nearly two-thirds of children can experience long-term seizure control after selective temporal lobectomy (as studied in a Class I randomized, controlled trial).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is abundant evidence supporting the role for surgical revascularization of both symptomatic and asymptomatic moyamoya in children with operations such as pial synangiosis. [5][6][7][8] Regarding the MTS, the American Academy of Neurology practice parameter recommends surgery as the treatment of choice for medically intractable temporal lobe epilepsy. 4 The patient's seizures in this case were controlled with medication at the time of diagnosis of moyamoya, but the natural history of MTS suggests that a minority of children will continue to attain seizure control on medication alone, whereas nearly two-thirds of children can experience long-term seizure control after selective temporal lobectomy (as studied in a Class I randomized, controlled trial).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are data to support a role for surgical revascularization of progressive moyamoya in children (even if they are asymptomatic). 6 Coexistence of these 2 distinct pathologies is both interesting and has implications for planning long-term treatment strategies.…”
mentioning
confidence: 99%
“…4) Although there are increased risks for subsequent clinical and radiologic worsening, most cases are initially asymptomatic as shown in this present case. 10) The initial symptoms are often ischemic events, such as transient ischemic attacks and completed ischemic strokes. 11) As regard the arterial occlusive lesions in NF-1, it has been suggested that the obliteration of the large-sized arteries is caused by the growth of the neurofibroma or ganglioneuroma in the tunica adventitia, and that of the small-sized arteries including cerebral arteries is caused by the proliferation of the smooth muscle cells.…”
Section: Moyamoya Syndrome In Nf-1mentioning
confidence: 99%
“…In pediatric population, there are multitude of symptoms associated with moyamoya disease, including transient ischemic attack, ischemic strokes, intracranial hemorrhages, seizures, headaches, choreiform movements, and cognitive deficits. Recently researchers have also reported asymptomatic cases of moyamoya and approximately half of them remained clinically asymptomatic over a mean follow up period of 5.4 y [2]. Thus, it is not unusual to see these variable presentations of moyamoya.…”
mentioning
confidence: 99%